Divergent nanostructures from identical ingredients: unique amphiphilic micelle template for polyaniline nanofibers, tubes, rods, and spheres - Anilkumar, P.; Jayakannan, M. (Macromolecules, 2008)
Here, we report a unique soft templating approach based oil all in-built amphiphilic azobenze-nesulfonic acid for tuning various types of polyaniline nanomaterials Such as fibers, rods, spheres, and tubes. The dopant molecule is freely soluble in water, and DLS measurements Of the resultant Solution revealed that it forms spherical micelles of diameter similar to 4.29 nm. The addition of aniline induces self-organization in the dopant micelles which produce micrometer-sized cylindrical aggregates or layerlike assemblies depending upon the aniline/dopant composition in the feed. In the emulsion route. the oxidation of these cylindrical or layerlike micelle aggregates produce nanofibers and nanotubes, respectively. The dilution of thick emulsion microaggregates led to the formation Of uniformly distributed small 175 nm aggregated micelles. which template for the nanorods (dilution route). Alternatively, the dopant micelles form spherical shape aggregates with oxidizing agent ammonium persulfate (APS) in water. Aniline molecules diffuse through the organic/aqueous interface and get absorbed at these spherical aggregates, and subsequent chemical oxidation produces exclusively polyaniline nanospheres (interfacial route). The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (TEM). DLS studies of the polymerization mixtures in water evident for the formation of micrometer range aggregates. TEM analysis confirmed the shape of the template as cylindrical, cylindrical + spherical, and spherical geometry for the complexes of dopant with aniline and APS in the emulsion, dilution, and interfacial routes, respectively. The amphiphilic nature of the dopant solubilizes the nanomaterials in water and organic solvents, and the optical properties of nanomaterials were studied in various solvents by UV-vis spectroscopy. The wide-angle X-ray diffraction Studies confirmed the appearance of a new peak at lower angle (d = 13.6 angstrom) corresponding to the highly crystalline and ordered polyaniline nanomaterials. The solid-state properties of the nanomaterials were found to he highly dependent on the size and shape of polymerization templates employed for the synthesis.

Hydroxyl-functionalized polyaniline nanospheres: tracing molecular interactions at the nanosurface via vitamin C sensing - Anilkumar, P.; Jayakannan, M. (Langmuir, 2008)
Here, we report a synthesis of novel polyaniline nanospheres bearing mono- and bishydroxyl functional groups were to trace the molecular interactions at the nanosurfaces through vitamin C sensing. Two new aniline monomers synthesized via a tailor-made approach and polymerized to produce soluble and uniform polyaniline nanospheres. The structures of the monomers and polymers were characterized by NMR, FT-IR, and MS techniques, and the morphology of the nanomaterials was analyzed by SEM and TEM. The mechanistic aspects of the nanomaterial formations were analyzed by FT-IR and dynamic light scattering techniques. These studies revealed that the hydroxyl-functionalized monomers have strong hydrogen bonding at the monomer level and form spherical aggregates in water, which are templates for the polyaniline nanospheres 600 +/- 100 nm in size. A controlled synthesis was also carried out using aniline hydrochloride as an unsubstituted counterpart, which yields polyaniline nanofibers. WXRD analysis confirmed the presence of a sharp peak at lower angle at 2 theta = 7.3 degrees (d-spacing of 13.4 angstrom) in hydroxyl-substituted nanospheres with respect to enhancement of solid-state ordered crystalline domains, whereas unsubstituted nanofibers were found to be highly amorphous. Vitamin C was employed as an analyte to trace the molecular interaction at the nanosphere surface and Study the influence of nanosurface functionalization on the sensing ability of biomolecules. The bishydroxyl-functionalized polyaniline nanospheres were found to show efficient molecular interactions toward vitamin C, whereas nanospheres with a monohydroxyl group or unsubstituted nanofibers failed as sensing materials. In a nut shell, in the present investigation, for the first time, we have proved the importance of surface functionalization of polyaniline nanomaterial, exclusively nanospheres, using hydroxyl groups for studying the molecular interactions at the nanosurfaces with biomolecules such as vitamin C.

Self-assembled cylindrical and vesicular molecular templates for polyaniline nanofibers and nanotapes - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2009)
We report a soft template approach based on a custom-designed novel surfactant-cum-dopant for size and shape tuning of polyaniline nanomaterials such as nanofibers and nanotapes via emulsion and dispersion polymerization routes. A new amphiphilic 4-(3-dodecyl-8-enylphenyloxy) butane sulfonic acid was synthesized by ring-opening of butanesultone with renewable resource cardanol. The new amphiphilic dopant forms spherical micelles in water and its critical micelle concentration was determined by dye encapsulation and surface tension methods. In the emulsion route, the amphiphilic dopant complexed with aniline to produce cylindrical micellar aggregates that template exclusively for polyaniline nanofibers. The dispersion of aniline + dopant in water/toluene solvent mixture produces vesicles that selectively template for polyaniline nanotapes. The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (HR-TEM). DLS of the polymerization templates in water proved the presence of micrometer range aggregates, and TEM images confirmed the shape of the cylindrical and vesicular templates. The polyaniline nanomaterials were found soluble in water and polar organic solvents for structural characterization and composition analysis by H-1 NMR spectroscopy. Absorbance spectra of the nanomaterials showed free carrier tail above 900 nm in the near IR region for the delocalization of electrons in the polaron band Corresponding to expanded conformation of polyaniline chains, Wide angle X-ray diffraction showed two new peaks at low angle region with d-spacing of 26.5 and 13.6 angstrom Corresponding to lamellar ordering of polyaniline chains followed by interdigitations of the amphiphilic dopant in the nanomaterials.

Novel supramolecular organogel nanotubular template approach for conducting nanomaterials - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2010)
We report a unique supramolecular organogel template approach for conducting polyaniline nanomaterials. A novel organogel based on sulfonic acid dopant was designed and developed from renewable resource 3-pentadecyl phenol via ring-opening of 1,4-butane sultone. The amphiphilic dopant molecule formed thermo-reversible supramolecular organogel in highly polar solvents like alcohols. The self-assembled fibril network morphology of the gel was confirmed by scanning electron microscopy (SEM) and atomic force microscopy. Transmission electron microscopy (TEM) revealed that the inner part of the fibrous gel is nanotubular with the pore diameter of similar to 75 run. The organogel nanotubular morphology was retained even in the presence of aniline+dopant complex, and the aniline monomers occupied the hydrophobic nanopockets provided by the amphiphilic dopant. The chemical oxidative polymerization of the dopant+aniline organogel template produced well-defined polyaniline nanofibers. The polymerization was carried out at various temperatures to establish the role of the physical state and stability of the organogel on the morphology. The sulfonic acid molecule acts both as self-assembled molecular template for the synthesis of polymer nanomaterial as well as anionic counterpart for stabilizing the positively charged conducting polymer chains. The gel template played a pivotal role in directing polyaniline chains to form nanofibers and also manipulating the number of other properties such as conductivity, solubility, percent crystallinity, and solid-state ordering, etc. Temperature-dependent electrical conductivity measurements revealed that the nanomaterials showed typical linear ohmic behavior and also followed the 3-D VRH model at elevated temperatures.